Perspective of Islamic Criminal Law on Acquittal and Punishment of Paedophile: A Study Based on Islamic Criminal Law - Ramadhani, Yunisa; Aldi, Satria; Salma, Salma; Nur Hasanah, Asra; Hidayat, Rahmat; Stiawan, Thoat (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
Cases of paedophile are becoming increasingly prevalent in Indonesia, with data from the Indonesian Child Protection Commission showing a consistent annual rise, particularly in child sexual abuse cases. This study aims to analyze a court verdict that acquitted a paedophile offender, identify appropriate legal sanctions, and examine the Islamic legal (fiqh jinayah) perspective on chemical castration as a form of punishment. Using a qualitative method with a content analysis approach, the study examines legal documents, including Decision No. 36/Pid.Sus/2023/PN.LBB, Law No. 35 of 2014 on Child Protection, and Law No. 17 of 2016, as well as secondary sources such as scholarly journals, articles, and books. The analysis reveals that: (1) the acquittal was primarily based on conflicting witness testimonies, which weakened the evidence; (2) appropriate sanctions should be based on Articles 81(1) and 82(2) of the Child Protection Law in conjunction with the Indonesian Criminal Code, including chemical castration as regulated in Law No. 17 of 2016; and (3) from a fiqh jinayah perspective, chemical castration is considered permissible to safeguard public welfare. These findings offer insights for further legal and Islamic jurisprudential discussions on effective responses to sexual crimes against children.